Adobe Acrobat 8 how-tos : 125 essential techniques - Baker, Donna L., 1955- (Adobe Press, 2007)
Increase your productivity with Acrobat, one technique at a time. Now that PDF has become the ubiquitous electronic document format, it's important to recognize that there's much more to Adobe Acrobat than just managing your documents and improving workflow. With this powerful tool, you can now communicate with new commenting tools, collaborate with individuals and teams, automate forms, provide additional security, use redactive tools, and accom-plish tasks for greater productivity and efficiency. But with all this power, how do you bring your Acrobat skills up to speed quickly? Never fear, Acrobat expert Donna L. Baker has picked out the most integral techniques for accomplishing nearly any office communication task. You'll be expanding your PDF skills in no time in this focused, handy guide. Here are just some of the things you'll learn to do: Conduct searches quickly by building an index and attaching it to files Merge multiple files into a single PDF document and create a custom cover Create comments in PDF documents, start a review, and work with comments Use new form tools in Acrobat 8 for drawing fields, tracking responses, and creating a form automatically Set up an online meeting in Acrobat Connect- Add movies and 3D content, and create interactive presentations Assign levels of security and passwords to documents using new hashing algorithm support in Acrobat 8.